An accurate 1-V threshold voltage reference for ultra-low power applications. (May 2017) - Parisi, Alessandro; Finocchiaro, Alessandro; Palmisano, Giuseppe
Abstract: An ultra-low power voltage reference circuit is presented, which is based on proportional (PTAT) and complementary (CTAT) to absolute temperature current generation and performs current-mode voltage reference with first-order temperature compensation. Thanks to the use of subthreshold CMOS transistors and an operational amplifier, the circuit achieves low sensitivity to power supply variations while providing low voltage capability. Measurements show that the proposed circuit provides a reference voltage of around 597 mV and correctly operates with a supply voltage ranging from 3.3 V to 1 V and temperature variations from −40 to 85 °C. The overall current consumption is below 1 μA, thus making it suitable for RF-powered and ultra-low power sensor network applications. The chip was fabricated in a standard 0.13-μm CMOS technology and occupies a core area as low as 0.02 mm 2 .